P.G. De Gennes' Impact On Science - Volume I : Solid State And Liquid Crystals. (Series on directions in condensed matter physics., 2009)
This publication, in two volumes, is devoted to the scientific impact of the work of Nobel Laureate, Pierre-Gilles de Gennes, one of the greatest scientists of the 20th century. It covers the important fields for which de Gennes was renowned: solid state (magnetism and superconductivity), macroscopic random media and percolation, supersolids, liquid crystals, polymers, adhesion and friction, and biophysics. The book brings together internationally renowned experts to contribute their perspectives on the significance of de Gennes' works. They have each selected a definitive paper, which gives t.